2015
DOI: 10.2527/jas.2015-9394
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and pork fat quality as measured by three methods of pigs fed 20% DDGS and slaughtered using a standard industry split marketing strategy

Abstract: A total of 40 pens containing 22 crossbred barrows (initial BW = 43.07 ± 1.61 kg; PIC 1050 × PIC 337 genetics) were housed in a commercial wean to finish facility. Pens were randomly allotted to dietary treatments in a 2 × 3 factorial arrangement with 2 levels of dried distillers grains with solubles (DDGS; 0% or 20%) and chosen for 1 of 3 marketing cuts removing 4, 8, and 10 animals from each pen. Fat tissue samples were removed from the anterior tip of the jowl and posterior to the sternum on the belly edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Belly fat. Not surprisingly, several studies have shown inclusion of DDGS in the diet increases belly IV (Whitney et al, 2006;Benz et al, 2010; regardless of IV determination method (Shircliff et al, 2015). Variations of added fat will change IV depending on the saturation of the source with CWG increasing IV compared to beef tallow, however, when fat was added at 6%, IV did not differ regardless of fat sources or fat depot (Kellner et al, 2014).…”
Section: Fat Depotsmentioning
confidence: 97%
See 4 more Smart Citations
“…Belly fat. Not surprisingly, several studies have shown inclusion of DDGS in the diet increases belly IV (Whitney et al, 2006;Benz et al, 2010; regardless of IV determination method (Shircliff et al, 2015). Variations of added fat will change IV depending on the saturation of the source with CWG increasing IV compared to beef tallow, however, when fat was added at 6%, IV did not differ regardless of fat sources or fat depot (Kellner et al, 2014).…”
Section: Fat Depotsmentioning
confidence: 97%
“…Regardless of inclusion level or depot, DDGS increases PUFA and raises IV of pork fat (Whitney et al, 2006;Xu et al, 2010;Shircliff et al, 2015). A cooperative study reported while SFA and MUFA levels decreased in subcutaneous fat, PUFA levels increased with increasing (15%, 30% and 45%) levels DDGS in the diet (Cromwell et al, 2011).…”
Section: Dried Distillers Grains With Solublesmentioning
confidence: 99%
See 3 more Smart Citations